Wadensjö, Cecilia: Interpreting as Interaction. On dialogue-interpreting in immigration hearings and medical encounters. Lindköping University, 1992 - Dam, Helle V.; Schjoldager, Anne (HERMES - Journal of Language and Communication in Business, 2017)
No abstract.